Young children are researchers: Children aged four to eight years engage in important research behaviour when they base decisions on evidence. Issue 5 (2nd September 2016) - Murray, Jane
Abstract : Whilst young children are affected by educational policy decisions based on research evidence, their abilities to make decisions based on evidence are often disregarded by policymakers and professional adult researchers. This article reports on elements of the Young Children As Researchers (YCAR) project, an interpretive empirical study that sought social justice in the field of early childhood by conceptualising ways in which young children aged four to eight years are researchers and may be considered to be researchers. Adopting a principled approach framed by a 'jigsaw' methodology, the YCAR study engaged professional adult researchers ( n  = 34), young children aged four to eight years ( n  = 138) and their practitioners ( n = 15) in three English primary schools. Drawing on the study findings, this aticle argues that decision-making based on evidence is an important research behaviour undertaken by young children that deserves recognition by policymakers, practitioners and the academy as a potential vehicle for realising children's participation rights.